Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(2x^2+5x+2\)
\(=2x^2+x+4x+2\)
\(=x\left(2x+1\right)+2\left(2x+1\right)\)
\(=\left(2x+1\right)\left(x+2\right)\)
\(2x^2+5x+2\)
\(=\left(2x^2+x\right)+\left(4x+2\right)\)
\(=x\left(2x+1\right)+2\left(2x+1\right)\)
\(=\left(2x+1\right)\left(x+2\right)\)
2x( x - 1 ) - x( 1 - x )2 - ( 1 - x )3
= 2x( x - 1 ) - x( x - 1 )2 + ( x - 1 )3
= ( x - 1 )[ 2x - x( x - 1 ) + ( x - 1 )2 ]
= ( x - 1 )( 2x - x2 + x + x2 - 2x + 1 )
= ( x - 1 )( x + 1 )
Ta có: \(2x\left(x-1\right)-x\left(1-x\right)^2-\left(1-x\right)^3\)
\(=\left(x-1\right)\left(2x-x^2+x+x^2-2x+1\right)\)
\(=\left(x-1\right)\left(x+1\right)\)
\(x^2-10x+25\)
\(=x^2-2\cdot x\cdot5+5^2\)
\(=\left(x-5\right)^2\)
x^2 - 10x + 25
= x^2 - 5x - 5x + 5^2
= x(x - 5) - 5(x - 5)
= (x - 5)(x - 5)
1) \(\left(3x+7\right)^2-\left(2x-3\right)^2=0\)
\(\Leftrightarrow\left(3x+7-2x+3\right)\left(3x+7+2x-3\right)=0\)
\(\Leftrightarrow\left(x+10\right)\left(5x+4\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x+10=0\\5x+4=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-10\\x=\frac{-4}{5}\end{cases}}\)
Vạy ...
phần 2 tương tự áp dụng \(a^2-b^2=\left(a-b\right)\left(a+b\right)\)
\((4x-1)^2-(5-3x)^2=0\)
\(\Leftrightarrow(4x-1-5-3x)(4x+1+5-3x)=0\)
\(\Leftrightarrow(x-6)(x+6)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-6=0\\x+6=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=6\\x=-6\end{cases}}\)
Vậy : ...
1) \(x^3+x^2+4\)
\(=\left(x^3-x^2+2x\right)+\left(2x^2-2x+4\right)\)
\(=x\left(x^2-x+2\right)+2\left(x^2-x+2\right)\)
\(=\left(x^2-x+2\right)\left(x+2\right)\)
2) \(x^3-2x-4\)
\(=\left(x^3+2x^2+2x\right)-\left(2x^2+4x+4\right)\)
\(=x\left(x^2+2x+2\right)-2\left(x^2+2x+2\right)\)
\(=\left(x^2+2x+2\right)\left(x-2\right)\)
x2 + 1 - y2 - 2x = (x2 - 2x + 1) - y2 = (x - 1)2 - y2 = (x - 1 - y).(x - 1 + y)
x8 + x4 + 1
=x8+2x4+1-x4
=(x4+1)2-x4
=(x4-x2+1)(x4+x2+1)
=(x4-x2+1)(x4+2x2+1-x2)
=(x4-x2+1)[(x2+1)2-x2]
=(x4-x2+1)(x2-x+1)(x2+x+1)
x8 + x4 + 1
= ( x4 )2 + 2x4 + 1 - x4
= ( x4 + 1 )2 - x4
= ( x4 + 1 - x2 ) ( x4 + 1 + x2 )
#)Giải :
\(4p^2-36p+56=\left(2p\right)^2-2.2p.9+9^2-25=\left(2p-9\right)^2-5^2=4\left(p-7\right)\left(p-2\right)\)
4p2 - 36p + 5c
= (2p)2 - 2 . 2p . 9 + 81 - 45
= (2p - 9)2 - (\(\sqrt{45}\))2
= (2p - 9 - \(\sqrt{45}\))( 2p - 9 + \(\sqrt{45}\))
= ( 2p - 9 - 3\(\sqrt{5}\))( 2p - 9 + 3\(\sqrt{5}\))